Relationship between Bone Mineral Density and Parity in Women of Reproductive Age Group (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: The objective of this study was to assess the relationship between Bone Mineral Density (BMD) and parity in women of reproductive age group.Materials and methods: A cross sectional analytical study was carried out where the study population was women of reproductive age group (15 to 49 years of age). A total of 180 women were included as study subjects and the sampling technique was non random sampling. The study population was selected from healthy women of reproductive age group. Data about age, height, weight and history of parity were taken. BMD was measured by DEXA. Then relationship between BMD and parity were analysed.Results: In this study, a large number, 79 (43.9%) of participants were in age group of 29-38 years with mean± SD 35.46±6.75 years. Association between BMD and age of the study subjects represented that values of BMD decreased with increasing age (P